2015
DOI: 10.1002/cssc.201500245
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Transition‐Metal‐Coated Tungsten Carbides for Efficient and Selective Electrochemical Reduction of CO2 to Methane

Abstract: The design of catalysts for CO2 reduction is challenging because of the fundamental relationships between the binding energies of the reaction intermediates. Metal carbides have shown promise for transcending these relationships and enabling low-cost alternatives. Herein, we show that directional bonding arising from the mixed covalent/metallic character plays a critical role in governing the surface chemistry. This behavior can be described by consideration of individual d-band components. We use this model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 56 publications
2
49
0
Order By: Relevance
“…Transition metal carbides are another class of promising catalysts with low cost, favorable carbophobic and oxophilic properties. In 2015, to understand the relationships between the binding energies of reaction intermediates and active sites of metal carbides, Wannakao et al studied the CO 2 reduction mechanism of Fe‐, Co‐, and Pt‐doped W carbides through DFT method . The results showed that the d‐band center of transition metal was related to the adsorption energies, which relatively influenced the binding site preferences and geometries of the active intermediates.…”
Section: Electrocatalysts For Electrocatalytic Co2 Reductionmentioning
confidence: 99%
“…Transition metal carbides are another class of promising catalysts with low cost, favorable carbophobic and oxophilic properties. In 2015, to understand the relationships between the binding energies of reaction intermediates and active sites of metal carbides, Wannakao et al studied the CO 2 reduction mechanism of Fe‐, Co‐, and Pt‐doped W carbides through DFT method . The results showed that the d‐band center of transition metal was related to the adsorption energies, which relatively influenced the binding site preferences and geometries of the active intermediates.…”
Section: Electrocatalysts For Electrocatalytic Co2 Reductionmentioning
confidence: 99%
“…[137] But after introducing single metal atom into the surface, the onset potential would be reduced remarkably. [139,140] Compared with bulk noble metals, core-shell structure could reduce the catalyst cost. Besides bulk carbide, metal-coated composite systems were further explored.…”
Section: Metal-nonmetal Compounds (Oxides Chalcogenides and Carbides)mentioning
confidence: 99%
“…For an Ir defect, the simulated onset potential for CO 2 reduction to methane was −0.09 V (Figure 15), simultaneously HER was strongly suppressed with overpotential of 0.38 V. This work paved the way to improved metal carbide electrocatalysts via single atom catalyst. [139] Cu/WC and Pd/WC composite particles could be used for CO production with low overpotential. Advanced synthesis technology is able to prepare metal-coated WC nanoparticles with highly controllable size and composition.…”
Section: Metal-nonmetal Compounds (Oxides Chalcogenides and Carbides)mentioning
confidence: 99%
See 2 more Smart Citations